PENGARUH OPENNESS DAN ENTREPRENEURIAL SELF-EFFICACY TERHADAP ENTREPRENEURIAL INTENTION DIMODERASI ENTREPRENEURSHIP EDUCATION DAN GENDER - Andi Wijaya; Agustin Ekadjaja; Cindy Geovanny (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract - The purpose of this study was to determine the effect of openness to experience and entrepreneurial self-efficacy on entrepreneurial intention and examine the moderating role of entrepreneurship education and gender on the influence between entrepreneurial self-efficacy and entrepreneurial intention. The sample in this study was obtained by cross-sectional study and purposive sampling method using a questionnaire and obtained a sample of 104 students at one university in West Jakarta. The results of this study indicate that openness to experience has a positive and insignificant effect on entrepreneurial intention, entrepreneurial self-efficacy has a positive and significant effect on entrepreneurial intention, entrepreneurship education has a positive and insignificant effect as a moderating variable on the effect of entrepreneurial self. -efficacy on entrepreneurial intention and gender have a positive and insignificant effect as moderating variables on the effect of entrepreneurial self-efficacy on entrepreneurial intention. Students who have high curiosity and openness tend to be interested in trying new things to build a business and this does not depend on gender. Universities through their teaching staff are required to be able to inspire in creating individual entrepreneurial self-efficacy, through the task of making business models & direct business practices will provide an overview of the business world to strengthen students' intentions to become entrepreneurs and present teachers who are business practitioners judged to be able to act as role models. For students to emulate and thus will strengthen the individual's belief in entrepreneurial abilities Keywords: Openness to Experience; Entrepreneurial Self-Efficacy; Entrepreneurship Education; Gender; Entrepreneurial Intention